2018
DOI: 10.3847/1538-4357/aabba3
|View full text |Cite
|
Sign up to set email alerts
|

Torsional Alfvén Wave Embedded ICME Magnetic Cloud and Corresponding Geomagnetic Storm

Abstract: The energy transfer during interaction of large-scale solar wind structure and the Earth's magnetosphere is the chronic issue in space-weather studies. To understand this, researchers widely studied the geomagnetic storms and sub-storms phenomena. The present understanding suggests that long duration of southward interplanetary magnetic field component is the most important parameter for the geomagnetic storm. Such long duration strong southward magnetic field is often associated with ICMEs, torsional Alfvén f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 60 publications
(61 reference statements)
0
14
0
Order By: Relevance
“…In addition to this, Raghav et al. (2019) suggested that Alfvénic fluctuations are associated with the extended/long duration recovery of a storm (Raghav et al., 2018; Shaikh et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to this, Raghav et al. (2019) suggested that Alfvénic fluctuations are associated with the extended/long duration recovery of a storm (Raghav et al., 2018; Shaikh et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Jordanova et al (2003) proposed that the ring current decay during the initial fast recovery is highly affected by the time-varying night-side inflow of plasma from the magneto-tail, and particle precipitation by wave-particle interactions (Dessler & Parker, 1959). In addition to this, Raghav et al (2019) suggested that Alfvénic fluctuations are associated with the extended/long duration recovery of a storm (Raghav et al, 2018;Shaikh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…High-intensity long-duration continuous AE activities (HILDCAAs) are the effects of Alfvén wave trains in the IMF (Tsurutani & Gonzalez 1987). Alfvénic fluctuations are associated with repetitive substorms (Lee et al 2006) and inferred to extend the recovery phase of geomagnetic storms (Tsurutani et al 2011;Raghav et al 2018;Telloni et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…ICMEs occasionally interact with the terrestrial magnetic field with sufficient mass, velocity, and southward interplanetary magnetic field (IMF) to cause geomagnetic storms and equatorward extensions of the auroral oval (Gonzalez et al, 1994;Yokoyama et al, 1998;Daglis et al, 1999;Pulkkinen, 2007). Analyses of such solar and geomagnetic storms are more than just of academic interest due to their potential to create space weather conditions that frequently enhance electric currents in space, which in turn can affect essential societal infrastructure such as power grid systems, satellite operations, and long-range communication systems (Pulkkinen, 2007;Baker et al, 2008;Schrijver, 2015;Pulkkinen et al, 2017;Riley et al, 2018;Raghav et al, 2018Raghav et al, , 2019Oliveira et al, 2020aOliveira et al, , 2021aHapgood et al, 2021).…”
mentioning
confidence: 99%